The Emerald review of industrial and organizational psychology - Dipboye, Robert L. (Emerald Publishing Limited, 2018)
This book provides an in depth survey of the field of Industrial and Organizational Psychology (I/O), a specialized field within the larger discipline of psychology also called Work and Organizational Psychology, Occupational Psychology, and Organizational Psychology. I/O is the scientific study of how individuals and groups behave in the performance of work activities and in the context of organizations. It is also the application of this research to improving the effectiveness and the well-being of people and the organizations in which they work. It is part science, contributing to the general knowledge base of psychology, and part application, using that knowledge to solve real-world problems.